Mantle degassing on a near shore volcano, SE Tyrrhenian Sea. (7th April 2015) - Loreto, Maria F.; Italiano, Francesco; Deponte, Davide; Facchin, Lorenzo; Zgur, Fabrizio
Abstract The presence of a seamount‐like structure, located a few nautical miles offshore the Capo Vaticano Promontory (western Calabria, S Italy), was revealed by combined geophysical and geochemical investigation. The edifice covers 55 km2, with a top located at a depth of about 70 m below sea level, and consists mainly of a NW‐trending structure orthogonally interrupted by minor ridges, the largest of which is affected by extensional faults. The top of the edifice hosts active vents, injected fluids that have been investigated for dissolved volatiles. Gas analyses revealed high CO2 and CH4 contents, several orders of magnitude above the atmospheric‐type values expected for shallow, coastal marine waters, and a noteworthy enrichment in mantle‐derived 3He, which is an unambiguous indicator of the mantle origin of the fluids. Our results, combined with available data from the literature, suggest that the edifice is a tectonically controlled volcanic system, which presence near the Calabria region changes the role played by faults in the frame of the subduction process.